PLEASE Strategy in Writing: An Experimental Study in EFL Senior High School in South Sumatra - Fatimah Azzahra; Annisa Astrid; Winny Agustia Riznanda (STKIP AGAMA HINDU SINGARAJA, 2025)
Writing remains one of the most challenging skills for English as a Foreign Language (EFL) students, particularly in organizing ideas coherently and expressing them clearly. In Indonesian senior high schools, students often struggle with paragraph development due to limited strategic guidance and reliance on standard teaching techniques. To address this issue, this study investigated the effectiveness of the PLEASE (Pick–List–Evaluate–Activate–Supply–End) Strategy in improving the writing achievement of eleventh-grade students of MAN 2 Palembang. A quasi-experimental method with a quantitative approach was applied, involving two groups: one experimental group receiving PLEASE strategy instruction and one control group with teacher’s strategy. The writing test was administered before and after the treatment and evaluated through descriptive and inferential statistical analyses, including independent and paired-sample t-tests. The results revealed a significant improvement in the experimental group and a notable difference between the experimental and control groups. These findings indicate that the structured and metacognitive nature of the PLEASE strategy effectively enhances students’ ability to plan, organize, compose, and refine paragraphs. Future research may explore its application across different writing genres or integrate it with digital media to optimize writing instruction in diverse EFL contexts.